Improving Fuel Product Quality from Catalytic Cracking Units in Oil Refineries Using a Co-HfO2/Mesoporous SiO2 Nanocomposite Catalyst - Alkhafaji , Haider M. Hussein (Journal of Petroleum Research and Studies, 2025)
Catalytic cracking is fundamental in oil refineries for producing valuable fuels and chemicals. Conventional catalysts lack optimal selectivity resulting in inferior fuel quality. This work develops an innovative cobalt-hafnium oxide nanocomposite catalyst supported on mesoporous silica. The tailored nanostructure displays remarkable activity, selectivity and stability for upgrading hydrocarbon fractions. Composite synthesis first prepares cobalt nanoparticles, hafnium oxide and mesoporous silica separately then assembles these via impregnation. Catalyst characterization analyzes morphology, crystallinity and porosity. A fixed-bed reactor evaluates performance cracking model feed at 500 °C and 2 bar. Products undergo chromatographic quantification revealing 94% heavy oil conversion and 67% gasoline selectivity at 8 h-1 space velocity. Analysis shows obtained high purity, high-octane fuels match industry benchmarks. The stable selective nanocomposite catalyst successfully upgrades petroleum streams under mild conditions to improve refinery economics.